Diatom responses to rapid light and temperature fluctuations: adaptive strategies and natural variability - Juffermans, Emma; Hoch, Lilian; Songsomboon, Kittikun; Ralph, Peter J.; Herdean, Andrei (Frontiers in Photobiology, 2025)
Diatoms are crucial in global primary productivity and carbon sequestration, contributing significantly to marine food webs and biogeochemical cycles. With the projected increase in sea surface temperatures, climate change poses significant threats to these essential organisms. This study investigates the photobiological responses of nine diatom species to rapid changes in light and temperature, aiming to understand their adaptability and resilience to climate-induced environmental fluctuations. Using a high-throughput phenoplate assay, we evaluated the maximum quantum yield of photosystem 2 (Fv/Fm), non-photochemical quenching (NPQ) and additional photosynthetic parameters under varying temperature conditions. Our results revealed significant variability in the photophysiological responses among the species, with temperature emerging as a dominant abiotic factor relative to light, accounting for 13.2%–37.5% of the measured variability. Measurements of effect size of temperature and light on Fv/Fm showed that there is additional significant innate variability in the samples when a homogeneous culture is fractioned in 384 subpopulations. Furthermore, hierarchical clustering analysis of the effect size of temperature, light and innate variability on all measured photosynthetic parameters identified two distinct diatom groups. One group exhibited strong interaction between light intensity and temperature, suggesting active synergetic mechanisms to cope with fluctuating environments, while the other showed potential limitations in this regard. These findings highlight diatoms’ diverse strategies to optimize photosynthesis and manage light and thermal stress, providing insights into their potential responses to future climate scenarios. Furthermore, we demonstrate that using the method presented in this work we can functionally cluster different diatom species.